Comparison of physicochemical parameters of surface waters with different purposes on the example of the Tatar Górny and Tatar Dolny reservoirs - Gryglik, Dorota; Kapuścińska, Ewelina; Jagniątkowski, Paweł (Instal, 2025)
The aim of the study was to examine the variability of selected physicochemical parameters in surface waters depending on the season. Measurements were conducted on water from Tatar Reservoir in Rawa Mazowiecka. Analyzed water samples were collected from May to December 2023. The following water quality indicators were selected for analysis: temperature, pH, turbidity, specific electrical conductivity, dissolved oxygen concentration, biochemical oxygen demand, chemical oxygen demand using the permanganate method, ammonium nitrogen concentration, orthophosphate phosphorus concentration, iron (III) concentration and chloride concentration. The study results were compared with the general surface water quality indicators applicable in Poland. It was observed that some physicochemical properties of the studied reservoirs underwent dynamic changes during the study period. Furthermore, it was found that an actual threat to the water in the studied reservoirs is the elevated concentration of orthophosphate phosphorus, which, during the summer period, may lead to excessive development of phytoplankton organisms (eutrophication).
Keywords: water quality; eutrophication; swimming area; Tatar Reservoir